QTL Mapping of Seed Vigor of Backcross Inbred Lines Derived From Oryza longistaminata Under Artificial Aging - Jin, Jie; Long, Weixiong; Wang, Liuting; Liu, Xingdan; Pan, Guojing; Xiang, Wei; Li, Nengwu; Li, Shaoqing (Frontiers in Plant Science, 2018)
Seed vigor is an important character of seed quality that promotes rice to germinate rapidly from soil and developing to a strong seedling, especially in the current rice direct-sowing production system. However, previous studies for seed vigor mainly concentrate in cultivars, and less reports involving in wild rice. In this study, 152 backcross inbred lines (BILs) derived from wild rice O. longistaminata were genotyped with re-sequencing technology, and QTLs for seed vigor related traits under normal and artificial aging treatment were analyzed. Totally, 36 QTLs were detected, of which, eight for germination potential (GP), 10 for germination rate (GR), 9 for seedling length (SL) and 9 for root length (RL). Among these, 14 novel QTLs were identified from O. longistaminata. Of which, six QTLs were related to germination, and eight related to seedling growth under aging stress. What’s more, the major QTLs q9SL1.1, q6SL1.1 and q3SL1.1 for seedling length were fallen in the same locus and fine-mapped an interval about 90 Kb. The major QTLs q9GR8.1 and q9GP8.1 related with germination were fine-mapped to an interval about 90 Kb. This work will provide us basis for breeding of high seed vigor rice in rice breeding programs and further cloning of these genes.